Dissecting Seed Mucilage Adherence Mediated by FEI2 and SOS5 - Griffiths, Jonathan S.; Crepeau, Marie-Jeanne; Ralet, Marie-Christine; Seifert, Georg J.; North, Helen M. (Frontiers in Plant Science, 2016)
The plant cell wall is held together by the interactions between four major components: cellulose, pectin, hemicellulose and proteins. Mucilage is a powerful model system to study the interactions between these components as it is formed of polysaccharides that are deposited in the apoplast of seed coat epidermal cells during seed development. When seeds are hydrated, these polysaccharides expand rapidly out of the apoplastic pocket, and form an adherent halo of mucilage around the seed. In Arabidopsis, mutations in multiple genes have similar loss of mucilage adherence phenotypes including CELLULOSE SYNTHASE 5 (CESA5)/MUCILAGE-MODIFIED 3 (MUM3), MUM5/MUCI21, SALT-OVERLY SENSITIVE 5 (SOS5), and FEI2. Here, we examine the interactions between these factors to better understand how they participate to control mucilage adherence. Double mutant phenotypes indicated that MUM5 and CESA5 function in a common mechanism that adheres pectin to the seed through the biosynthesis of cellulose and xylan, whereas SOS5 and FEI2, encoding a fasciclin-like arabinogalactan protein or a receptor-like kinase, respectively, function through an independent pathway. Cytological analyses of mucilage indicates that heteromannans are associated with cellulose, and not in the pathway involving SOS5 or FEI2. A SOS5 fluorescent protein fusion (SOS5-mCITRINE) was localized throughout the mucilage pocket, consistent with a structural role in pectin adhesion. The relationship between SOS5 and FEI2 mediated mucilage adherence was examined in more detail and while sos5 and fei2 mutants show similar phenotypes, key differences in the macromolecular characteristics and amounts of mucilage polymers were observed. FEI2 thus appears to have additional, as well as overlapping functions, with SOS5. Given that FEI2 is required for SOS5 function, we propose that FEI2 serves to localise SOS5 at the plasma membrane where it establishes interactions with mucilage polysaccharides, notably pectins, required for mucilage adherence prior to SOS5 being released into the apoplast.